Influence of Radiographic Viewing Perspective on Glenoid Inclination Measurement. (January 2019) - Chalmers, Peter N; Suter, Thomas; Jacxsens, Matthijs; Zhang, Yue; Zhang, Chong; Tashjian, Robert Z; Henninger, Heath B
Introduction: The purposes of this study were to determine (1) whether glenoid inclination (GI) could be accurately measured on plain radiographs as compared to a gold-standard 3-dimensional (3D) measure and (2) whether GI could be reliably measured on plain radiographs. Materials and Methods: Digitally reconstructed radiographs (DRRs) were made from 3D computed tomography reconstructions of 68 normal cadaver scapulae. DRRs were made in a variety of viewing angles. Inclination was measured on these DRRs. These measurements were also made using a gold-standard 3D method. Measurements were made by 2 orthopedic surgeons and 1 surgeon twice, to calculate interrater and intrarater intraclass correlation coefficients (ICCs). Results: The gold-standard 3D β was 83 ± 5° (72°–98°). On neutral plain radiographs, the mean ± standard deviation 2D β angle was 80 ± 6° (range, 66°–99°). With regard to accuracy, the 2D β angle was significantly different from the 3D β angle, with the 2D β underestimating the 3D β by 5° (95% confidence intervals −1 to 12). With regard to reliability, interrater ICCs for 2D β with a neutral viewing angle was 0.79. Two-dimensional β varied widely with viewing angle from 0.24 to 0.88. Interrater ICCs for the 3D method was 0.83 (0.60–0.92). Intrarater ICCs for all 3 techniques were high (>0.91). Conclusions: Two-dimensional radiographic GI measurement is not accurate, as it underestimates the 3D value by an average of 5° when compared to the gold-standard 3D measurement. GI 2D measurement reliability varies with viewing angle on plain radiographs and thus to accurately and reliably measure inclination 3D imaging is necessary.